The "Other" in Second Temple Judaism: essays in honor of John J. Collins - Harlow, Daniel C.; Collins, John J.; Hogan, Karina Martin; Goff, Matthew; Kaminsky, Joel S. (Eerdmans, 2011)
"Showing the wisdom of what he has learned" : the scholarly contributions of John J. Collins -- Israel's election and the other in biblical, Second Temple, and rabbinic thought / Joel S. Kaminsky -- God's other : the intractable problem of the gentile king in Judean and early Jewish literature / Carol A. Newsom -- The original sin of the Canaanites / Katell Berthelot -- Defining and controlling others within : hair, identity, and the Nazirite vow in a Second Temple context / Susan Niditch -- Otherworldly music and the other sex / Susan Ackerman -- How good was Ruth's Hebrew? : ethnic and linguistic otherness in the book of Ruth / Timothy H. Lim -- The other in Haggai and Zechariah 1-8 / Antonio Finitsis -- When the king is the other : Nebuchadnezzar's Hibernian cousin / Naomi S. Jacobs -- Elusive wisdom and the other nations in Baruch / Karina Martin Hogan -- The lady vanishes : wisdom in Ben Sira and Daniel / Shannon Burkes Pinette -- "The foolish nation that dwells in Shechem" : Ben Sira on Shechem and the other peoples in Palestine / Matthew Goff -- Poverty and otherness in Second Temple instructions / Samuel L. Adams -- Transcending death : the reasoning of the "others" and afterlife hopes in Wisdom 1-6 / Daniel J. Harrington -- The apocalyptic other / Lorenzo DiTommaso -- Apocalypticism as the rejected other : wisdom and apocalypticism in early Judaism and early Christianity / Sean Freyne -- The we and the other in the worldview of 1 Enoch, the Dead Sea scrolls, and other early Jewish texts / George W.E. Nickelsburg -- Monsters and the crippled cosmos : construction of the other in Fourth Ezra / Rebecca Raphael -- Idolatry and alterity : Israel and the nations in the Apocalypse of Abraham / Daniel C. Harlow -- Religious epistemology and the history of the Dead Sea scrolls community / Shane Berg -- The wicked priest revisited / James C. VanderKam -- Poetry of the heavenly other : angelic praise in the Songs of the Sabbath Sacrifice / Eric D. Reymond -- "At the crossroads" : anti-Samaritan polemic in a Qumran text about Joseph / Esther Chazon with Yonatan Miller -- Romans, Jews, and Christians on the names of the Jews / Martin Goodman -- Jews and Greeks as philosophers : a challenge to otherness / Erich S. Gruen -- The persecution of Judeans by Antiochus IV : the significance of "ancestral laws" / Robert Doran -- Constructing Jewish identity in Ptolemaic Egypt : the case of Artapanus / Patricia D. Ahearne-Kroll -- Dispelling an illusion of otherness? : judicial practice in the Heracleopolis papyri / Robert A. Kugler